Quality and completeness of, and spin in reporting of, pilot and feasibility studies in hip and knee arthroplasty: a protocol for a methodological survey - Lehana Thabane; Lawrence Mbuagbaw; Mohit Bhandari; Zinnia Chung; Lipalo Mokete (BMJ Open)
Introduction Pilot or feasibility trials examine the feasibility, viability and recruitment potential of larger, main trials. Specifically, a pilot trial can be instrumental in identifying methodological issues essential to the development of an effective research protocol. However, numerous studies published as pilot or feasibility studies have demonstrated notable inconsistencies in the nature of information reported, resulting in poor-quality and incomplete reporting. It is unclear whether such low quality or incompleteness of reporting is also prevalent in arthroplasty pilot trials.Methods and analysis This protocol outlines a methodological survey examining the completeness of reporting among hip and knee arthroplasty pilot trials in accordance with the Consolidated Standards of Reporting Trials (CONSORT) 2010 extension to pilot trials. Secondary objectives include: (1) determining the prevalence of ‘spin’ practices, defined as: (a) placing a focus on statistical significance rather than feasibility, (b) presenting results that show the trial to be non-feasible as feasible or (c) emphasising the effectiveness or potential intervention benefits rather than feasibility; (2) determining factors associated with incomplete reporting, and ‘spin’. A search of PubMed will be conducted for pilot trials in hip or knee arthroplasty published between 01 January 2017 and 31 December 2023. Following screening, appropriate data will be extracted from eligible publications and reported as descriptive statistics, encompassing elements of the CONSORT checklist associated with completeness of reporting. Logistic regression analysis and Poisson regression will be used to analyse factors associated with completeness of reporting and spin.Ethics and dissemination This methodological review does not require formal ethical approval, as it will solely involve the use of published and publicly reported literature. The results of this study will be disseminated through submission to peer-reviewed journals and academic conference presentations. Study details will be sent to McMaster University’s media coordinators to be shared through the institution’s research-focused platforms.